2020
DOI: 10.3390/biomedicines8110524
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Efflux Capacity and Cardiovascular Disease: The Ludwigshafen Risk and Cardiovascular Health (LURIC) Study

Abstract: (1) Background and Aims: Efforts to reduce coronary artery disease (CAD) by raising high-density lipoprotein (HDL) cholesterol (HDL-C) have not been uniformly successful. A more important factor than HDL-C may be cellular cholesterol efflux mediated by HDL, which has been shown to be associated with CAD. In this report, we analyzed the influence of cardiovascular biomarkers and risk factors on cholesterol efflux in a prospective observational study of patients referred to coronary angiography. (2) Methods: HDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 21 publications
(12 reference statements)
0
18
1
Order By: Relevance
“…Concerning the relationship between CEC and mortality, in the prospective observational study including 468 participants of the LUdwigshafen RIsk and Cardiovascular Health (LURIC) study, HDL CEC displayed an inverse relationship with CV mortality, with a reduction of about 27% in the higher CEC quartile both in patients with and without verified CAD, and after adjustment for traditional risk factors [ 219 ].…”
Section: Hdl Cec In Specific Conditionsmentioning
confidence: 99%
“…Concerning the relationship between CEC and mortality, in the prospective observational study including 468 participants of the LUdwigshafen RIsk and Cardiovascular Health (LURIC) study, HDL CEC displayed an inverse relationship with CV mortality, with a reduction of about 27% in the higher CEC quartile both in patients with and without verified CAD, and after adjustment for traditional risk factors [ 219 ].…”
Section: Hdl Cec In Specific Conditionsmentioning
confidence: 99%
“…Fibrates are believed to increase HDL-C mainly by increasing apoA-I and apoA-II gene transcription [28]. Some data have suggested that fibrates can reduce the risk of cardiovascular events, mainly in patients who have high TG (>200 mg/dL) and low HDL-C (<35 mg/dL) levels at baseline [29].…”
Section: Increasing Cholesterol In Hdl: Pharmacological Trialsmentioning
confidence: 99%
“…The ability of HDL particles to receive free cholesterol from cells has emerged as the culprit mechanism to explain HDL-related atheroprotective effects [103,104]; the cholesterol efflux capacity (CEC) has been shown to be inversely associated with CAD, independently of HDL-C concentrations [7,17,28,105], and with markers of preclinical atherosclerosis [29]. We must highlight the importance of taking into account all the different cholesterol-driving cellular pathways that may contribute to a specific condition.…”
Section: Hdl Function/dysfunction Beyond the Reverse Cholesterol Transportmentioning
confidence: 99%
“…Interestingly, it was reported that HDL concentration, composition, and function were not independent predictors for CVD outcome in CKD patients not receiving dialysis treatment [ 87 ]. However, an inverse association between cholesterol efflux capacity and CVD mortality has been reported for subjects without CKD [ 88 , 89 ]. According to Bauer et al [ 90 ], HDL cholesterol efflux capacity is not a prognostic marker of CVD risk in CKD patients.…”
Section: The Concept Of Hdl Dysfunctionality In Ckdmentioning
confidence: 99%